Pengaruh Berbagai Media Tanam Terhadap Pertumbuhan Bibit Kamboja Jepang (Adenium obesum) - Kristofel Puhiri; F.H. Listyorini; Besse Amriati (Agrotek, 2009)
The aim of this experiment was to find out the effect of media type to the growth of Adenium obesum. This experiment was conducted in Green house from 3 August to 3 November 2008 in completely randomized design which consists of five treatments in sixteen replicates. The treatments are A1 (soil), A2 (soil + burned rice husk), A3 (burned rice husk + fern), A4 (soil + burned rice husk + fern) and A1 (bokashi + burned rice husk + fern). The results showed that growing media significantly affected plant height at 8, 10 and 12 week; leaf number at 6, 8, 10 and 12 week; root length; stem diameter; leaf length as well as shoot weight. Media A4 (soil + burned rice husk + fern) gave the best results in plant height (week 4, 6, 8, 10 and 12), leaf number (week 4, 6, 8 and 12), root length, leaf number and shoot weight, while the lowest yield are performed by media A3 (burned rice husk + fern). Shoot weight from media treatment A4 (soil + burned rice husk + fern) and A2 (soil + burned rice husk) were increased about 230% and 205% in respectively, as compare to media A3 (burned rice husk + fern).